2012
DOI: 10.5402/2012/750593
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic and Hormonal Alterations with Diacylglycerol and Low Glycemic Index Starch during Canine Weight Loss

Abstract: Obesity increases insulin resistance and disregulation of glucose homeostasis. This study investigated low glycemic index starch (LGIS)/diacylglycerol (DAG) diet on plasma insulin and circulating incretin hormones during canine weight loss. Obese Beagle dogs were fed one of four starch/oil combination diets (LGIS/DAG; LGIS/triacylglycerol (TAG); high glycemic index starch (HGIS)/DAG; and HGIS/TAG) for 9 weeks during the weight loss period. At weeks 1 and 8, fasting plasma insulin, glucose, nonesterified fatty … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 41 publications
(42 reference statements)
2
2
0
Order By: Relevance
“…Thus, a diet that significantly reduces the postprandial insulin response, even without weight loss, may improve the metabolic profile of dogs. Our results agree well with a previous study in obese beagles fed diets formulated with either high or low glycemic starch, where 8‐week feeding of the low glycemic index diet led to improved insulin sensitivity compared to the high glycemic index diet (Mitsuhashi et al., ).…”
Section: Discussionsupporting
confidence: 93%
“…Thus, a diet that significantly reduces the postprandial insulin response, even without weight loss, may improve the metabolic profile of dogs. Our results agree well with a previous study in obese beagles fed diets formulated with either high or low glycemic starch, where 8‐week feeding of the low glycemic index diet led to improved insulin sensitivity compared to the high glycemic index diet (Mitsuhashi et al., ).…”
Section: Discussionsupporting
confidence: 93%
“…A more recent study showed lower peaks and smaller areas under the insulin curve with no change in glucose levels, indicating higher insulin sensitivity in obese dogs in an oral glucose tolerance test performed after 12 weeks of a pea-based diet compared to a rice-based diet (ADOLPHE et al, 2015). These findings are consistent with those of previous studies carried out by the same research group showing lower glycemic index of peas when compared to rice in healthy dogs (ADOLPHE et al, 2012) and higher insulin sensitivity in obese dogs on a low-glycemic index diet (MITSUHASHI et al, 2012). The dietary source of starch may be related to its digestibility, which in turn could have an effect on glucose levels (SILVA JÚNIOR et al, 2005;CARCIOFI et al, 2008;BAZOLLI et al, 2015).…”
supporting
confidence: 90%
“…In humans, dietary isoflavone supplementation also reduced the risk of developing metabolic disorders such as cardiovascular diseases, diabetes, and obesity (Bhathena and Velasquez, 2002) and seemed to improve fasting insulin levels and insulin resistance in postmenopausal diabetic women (Jayagopal et al, 2002). Further, diacylglycerols and carnitine have also been proposed to improve rates of weight loss and to be of help in body weight management in both dogs and cats (Laflamme, 2012;Mitsuhashi et al, 2012). Similarly to humans and rodents (Hibi et al, 2008) (Murase et al, 2001), the mechanism of action of diacylglycerols was suggested to be linked to an increase in fat oxidation and to a lowering of serum triacylglycerol levels postprandially which may result in increased satiety (Rudkowska et al, 2005).…”
Section: Dogs and Catsmentioning
confidence: 99%